The impact of individual training macrocycle on the sports results of 14 and 15 year old swimmers - Piotrowska, Katarzyna; Pabianek, Łukasz; Kochanowicz, Magdalena; Klimczyk, Mariusz; Zukow, Walery (Journal of Education, Health and Sport, 2018)
The aim of work was to show the impact of training on the sports results of 14 and 15 - year old swimmers. A hypothesis was that a properly conducted training period significantly improves the athletes’ result. The research was carried out on 4 people, one swimmer aged 14 and three athletes aged 15 from the sports club UKS 2 Tczew, based on an overworked training macrocycle in the period from September to March. The training consisted of 10 training units during week (morning and afternoon). The tests included two somatic measurements and a measurement of sports results during official swimming competitions. Based on the results of the research, it has been found that the impact of an individual training macrocycle is a very important factor, shaping the athletes’ sports result. The consequence of an appropriate distribution of loads in training units resulted in the better time achievements. As a result, there has been an improvement in deposits during the competition and promotion in sports championship classes.